Remote delivery of alcohol and/or substance misuse interventions for adults: A systematic review protocol - Howlett, Neil; Garcia-Iglesias, Jaime; Breslin, Gavin; Bartington, Suzanne; Jones, Julia; Brown, Katherine; Wills, Wendy (PloS one, 2021)
Introduction Alcohol and substance misuse are a public health priority. The World Health Organisation (WHO) estimates that harmful alcohol use accounts for 5.1% of the global burden of disease and that 35.6 million people worldwide are affected by substance misuse. The Coronavirus Disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has disrupted delivery of face-to-face alcohol and substance misuse interventions and has forced the development of alternative remote interventions or adaptation to existing ones. Although existing research on remote interventions suggests they might be as effective as face-to-face delivery, there has been a lack of systematic exploration of their content, the experience of service users, and their effectiveness for behavioural outcomes. This review will provide a narrative synthesis of the behaviour change techniques (BCT) contained in interventions for alcohol and/or substance misuse and their association with effectiveness. Methods and analysis Systematic searches will be conducted in MEDLINE, Scopus, PsycINFO (ProQuest), and the Cochrane Library. Included studies will be those reporting remote interventions focusing on alcohol and/or substance misuse among adults living in the community and which have a primary behaviour change outcome (i.e., alcohol levels consumed). Data extraction will be conducted by one author and moderated by a second, and risk of bias and behaviour change technique (BCT) coding will be conducted by two authors independently. A narrative synthesis will be undertaken focussing upon the association of BCTs with intervention effectiveness using promise ratios. Patient and Public Involvement (PPI) The Public Involvement in Research Group (PIRG), part of the NIHR-funded PHIRST, will be involved in refining the review questions, eligibility criteria, data synthesis and dissemination. Dissemination Dissemination will be through an academic peer reviewed publication, alongside other outputs to be shared with non-academic policy, professional, and public audiences, including local authorities, service users and community organisations.